Role and Functions of Folklore and Mythological Elements in the Work of M. A. Sabir - Kh. R. Sultanova (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The folklore and mythological traditions in the works of the outstanding poet-satirist of the late XIX — early XX centuries M. A. Sabir are considered in the article. It is noted that modern Sabirovology unites scientists from Azerbaijan, Russia and other countries who turn to the study of the poet’s works. The results of the analysis of a number of poetic works of Sabir, in which the author uses folklore and mythological elements as a technique that enhances the satirical sound of his texts are presented in the article. The author believes that Sabir, thanks to the inclusion of representatives of the demonic world (hortdan, damdabadzha, djinn, djann, Baba Yaga) among the characters, emphasizes the power of influence on people of belief in otherworldly forces, thus ridiculing inertness of thinking, unwillingness to develop, to keep up with progress. It is shown that Sabir creates realistic negative social types: money-grubbing, ignorant, etc. Special attention is paid to small folklore and mythological genres (curse, blessing, omen), which emphasize a person’s faith in the magical power of the word. It is noted that the study of folklore and mythological elements in the satirical works of Sabir has a perspective.